Diving retrosternal goiter and the dilemma of sternotomy: indications, predictors and surgical considerations - Leivaditis, Vasileios; Liolis, Elias; Baltayiannis, Nikolaos; Sarof, Pavlos; Pagoulatou, Alexandra; Grapatsas, Konstantinos; Antzoulas, Andreas; Litsas, Dimitrios; Papadopoulos, Panagiotis Dimitrios; Theofanis, George; Nikolakopoulos, Konstantinos; Katsakiori, Paraskevi; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2025)
A goiter is defined as an enlargement of the thyroid gland, typically resulting in a doubling in size or a weight exceeding 40 g. It affects approximately 5% of the global population. Diving, or substernal, goiters occur when more than 50% of the thyroid extends into the mediastinum, with an incidence ranging from 5% to 15.7% across various studies. An alternative definition describes diving goiters as those extending more than 3 cm below the sternal notch on chest computed tomography with the neck in hyperextension, or beyond the fourth thoracic vertebra. In this review, we outline the key clinical and radiological criteria that indicate when sternotomy is required for the surgical management of diving goiters.